The Illuminative Potential of Organizational Ethnographies - Dhunpath, Rubby (South African Journal of Higher Education, 2016)
Evaluation studies, especially of South African educational institutions and non-governmental organisations offering educational programmes have been criticised for focussing inadequately on the ethnographic and anthropological dimensions of organisations. The dominant approaches to evaluation have been structuralist and empirical-rational in orientation, serving narrow bureaucratic functions for funders and donors, based on self reports by programme participants. One way of resolving the dilemma of unreliable evaluation reports is producing richly contextualised organisational ethnographies which illuminate organisational contexts beyond superficial analyses. What are the potential benefits of an organisational ethnography, and what are the epistemological and ethical implications of such an endeavour? I shall attempt to answer these questions by drawing on an organisational ethnography of a South African non-governmental organisation offering language teacher development programmes, as I trace its mutating identity over three decades. I use insights derived from the traditions of empowerment evaluation (Fetterman, 1999) and illuminative evaluation (Parlett & Hamilton, 1976) as theoretical lenses to appraise the value of narratives in understanding organisational behaviour. Further, I appropriate Discourse Analysis to interrogate selected narrative data as a methodological lens in organisational analysis, and reflect on my experience of engaging in such a project. In the latter part of the chapter, I revisit the methodological wisdom of engaging in an institutional ethnography, highlighting some of the ethical, representational and epistemological dilemmas in negotiating a non-conventional approach. I conclude the paper with brief allusion to the potential value of organisational ethnographies in mediating an emerging performativity driven higher education culture.